DETERMINING SERVICE QUALITY DIMENSIONS OF SOCIAL COMMERCE WEBSITES - KARAKAYA ARSLAN, MELİSA; DİRSEHAN, TAŞKIN (FUTURE ACAD, 2017)
Since the last decades of the past century, social media and Web 2.0 created radical changes in consumer behavior and business models used. Especially with increasing usage of social media tools among both customers and firms during the past few years, the nature of electronic commerce has changed to make sure that customers are more active and participatory in the process. Hence, a subset of electronic commerce, named as social commerce, occurred as a more social, collaborative, relational, and creative form. The most important point where social commerce differentiates from electronic commerce is its ability to facilitate social networking and information sharing among individuals through tools such as comments, assessments and valuations, in a way similar to social media channels. These differences highlight the necessity of adding new dimensions to the present electronic service quality dimensions and the manifestation of the extents of social commerce service quality. Therefore, the aim of this paper is to specify the service quality dimensions of social commerce platforms. (C) 2017 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Social commerce; electronic commerce; service quality; customer satisfaction; customer loyalty; MULTIPLE-ITEM SCALE; ENVIRONMENTS; MODEL; WEB